On‐Chip Integrated Quantum‐Dot–Silicon‐Nitride Microdisk Lasers. Issue 16 (15th February 2017) - Xie, Weiqiang; Stöferle, Thilo; Rainò, Gabriele; Aubert, Tangi; Bisschop, Suzanne; Zhu, Yunpeng; Mahrt, Rainer F.; Geiregat, Pieter; Brainis, Edouard; Hens, Zeger; Van Thourhout, Dries
Abstract : Hybrid silicon nitride (SiN)–quantum‐dot (QD) microlasers coupled to a passive SiN output waveguide with a 7 µm diameter and a record‐low threshold density of 27 µJ cm −2 are demonstrated. A new design and processing scheme offers long‐term stability and facilitates in‐depth QD material and device characterization, thereby opening new paths for optical communication, sensing, and on‐chip cavity quantum optics based on colloidal QDs.